Prioridades competitivas da produção e práticas de gestão da cadeia de suprimentos : uma survey no setor eletroeletrônico brasileiro - Jabbour, Ana Beatriz Lopes de Sousa (2009)
The objectives of this study are to identify the supply chain management practices that have been adopted in companies of the eletroelectronic sector in Brazil and verify whether these companies production competitive priorities are related to the supply chain management practices. An empirical quantitative research was carried out through a survey using a multiple choice questionnaire and the Likert scale. The questionnaire was sent to managers of eletroelectronic sector companies associated to the Brazilian Electrical and Electronics Industry Association ABINEE. Statistical techniques were employed to analyze the relationship between the competitive priorities and supply chain management practices considering the influence of factors such as the company size and its position in supply chains of major interest. The major findings of this research were: (a) the most frequently adopted supply chain management practices are feedback from final customers on product suitability, identification of customer future needs, integration of product development activities with the suppliers, contribution of suppliers towards demand forecast, search for customer opinions about new products, and integration of product development activities with the clients; (b) the supply chain management practices are influenced by the size of the company since the bigger the company, the more supply chain management practices are adopted, and (c) there is low correlation between the variables of the construct competitive priorities and the variables of the construct supply chain management practices. This is due to the fact that most part of the sample is not focused on its supply chain.